A comparative study of a self strain-monitoring carbon nanotube film and carbon fibers under flexural loading by electrical resistance changes. (July 2015) - Pinto, B; Kern, S; Ku-Herrera, J J; Yasui, J; La Saponara, V; Loh, K J
Abstract: With the increased use of composites for load-carrying structures, the ability to obtain strain and damage information is critical to maintain reliable structures in the field. A promising class of multifunctional composites with the ability to self-sense strain and/or damage is possible through the use of carbon fibers and carbon nanotubes. This paper presents a comparative study of two sensors for fiber-reinforced polymer composites: the sensors are the carbon fibers themselves, and a non-structural carbon nanotube (CNT) film applied through spray deposition. The changes in resistance of the sensors are compared under monotonic and cyclic flexural loading. Within the limits of this study and the current CNT sensor configuration, the carbon fibers are shown to have a higher sensitivity for strain and damage sensing. However, the CNT film appears to track the performance of GFRPs reasonably well for tensile strains.